Cooling system design and analysis for high heat flux large dimension diffuser of a high-altitude test facility - Nematollah Fouladi; Mohammad Farahani; Milad Mahdian Dowlatabadi (International Journal of Thermofluids)
This study aims to investigate the design and analysis of a suitable cooling system for thermal protection of a large-dimension diffuser exposed to high heat fluxes in a combustion engine test at a high-altitude test facility. A water jacket cooling system is designed to ensure the permissible temperature conditions of the metal body while maintaining the desired range of total pressure drop. A wide range of coolant working pressures is evaluated to optimize the water-jacket cooling system performance and dimension. Additionally, the multi-channel cooling system is investigated regarding the initial conditions and the distribution of heat flux applied to the diffuser walls. Numerical simulation is also used to evaluate the performance of designed cooling systems. The capabilities of the developed numerical code are examined for designing and evaluating the cooling system's performance at working pressures ranging from 3 to 50 bar The results of the present study indicate that the optimum selection of the working pressure causes the optimal mass flow rate and dimensions of the cooling system. For instance, increasing the working pressure from 3 to 10 bar not only significantly reduces system lateral dimensions but also reduces the coolant mass flow rate by 68.79 %. Similarly, implementing multi-channel cooling systems reduces the required mass flow rate by up to 20 % and also reduces coolant system lateral dimension by up to 50 % in multi-channel cooling systems compared to the single-channel cooling system.